2016
DOI: 10.18632/oncotarget.9055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of red blood cell distribution width as a prognostic marker in chronic lymphocytic leukemia

Abstract: Red blood cell distribution width (RDW) is a quantitative measure of the variability in size of circulating erythrocytes. It was recently reported that RDW is a prognostic factor for infection diseases, cardiovascular and pulmonary diseases, as well as some neoplasms. Moreover, RDW is remarkably strong predictor of longevity, including all causes of death, for adults aged 45 years and older. To explain this occurrence it was proposed that persistent IGFs/mTOR signaling is one of the factors that play a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 43 publications
2
31
0
1
Order By: Relevance
“…In recent years, many studies investigating the relationship between RDW and cardiovascular disease and cancer were performed. RDW was proved to be an independent prognostic factor for many cancers such as lung cancer, prostate cancer, and chronic lymphocytic leukemia . In our study, we found that RDW measurements were significantly lower in patients with endometrial carcinoma compared to patients with endometrial hyperplasia and healthy controls.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In recent years, many studies investigating the relationship between RDW and cardiovascular disease and cancer were performed. RDW was proved to be an independent prognostic factor for many cancers such as lung cancer, prostate cancer, and chronic lymphocytic leukemia . In our study, we found that RDW measurements were significantly lower in patients with endometrial carcinoma compared to patients with endometrial hyperplasia and healthy controls.…”
Section: Discussionsupporting
confidence: 52%
“…Mean platelet volume (MPV) is an important inflammatory marker indicating platelet activation . Until today, the relationship between hematological parameters such as MPV, RDW, NLR, PLR, PDW were investigated, diagnostic, and prognostic features of these parameters with their role in metastatic activities of cancer were evaluated …”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact that RDW level is indicative of abnormal red blood cell survival and that it correlates with the presence of inflammatory states [18,19], this parameter has been investigated as prognostic factor in hematological malignancies [20][21][22][23][24][25][26]. Some recent studies and a meta-analysis have demonstrated that RDW is a potent predictor of all-cause mortality, including cancer-related deaths [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, since RDW level indicates abnormal red blood cell survival but it correlates also with the presence of severe systemic inflammatory state, undernutrition and inadequate production of EPO (3,25), this parameter has been investigated as prognostic factor and marker of disease activity in hematological malignancies [i.e., lymphocytic and myeloid leukemia, multiple myeloma, lymphoma and myelodysplastic syndrome (MDS)] (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Role Of Rdw In Hematological Tumorsmentioning
confidence: 99%
“…Recently, Podhorecka et al, with the aim to investigate RDW as a marker of prognosis in patients with chronic lymphocytic leukemia (CLL), enrolled 66 previously untreated persons (median age, 63 years; range, 38-85 years) with CLL diagnosis (27). They reported that RDW is in correlation with prognostic factors such as clinical stadium of the disease and expression of ZAP-70 and CD38, both indicators for immunoglobulin heavy chain genes mutations.…”
Section: Role Of Rdw In Hematological Tumorsmentioning
confidence: 99%